Soil Enzyme Activities and Their Relationships With Soil C, N, and P in Peatlands From Different Types of Permafrost Regions, Northeast China - Liu, Chao; Song, Yanyu; Dong, Xingfeng; Wang, Xianwei; Ma, Xiuyan; Zhao, Guangying; Zang, Shuying (Frontiers in Environmental Science, 2021)
Peatland is a key component of terrestrial ecosystems in permafrost regions and have important effects on climate warming. Soil enzymes are involved in biogeochemical cycle of soil carbon (C), nitrogen (N) and phosphorus (P), which can be used as early sensitive indicators of soil nutrient changes caused by climate change. To predict the possible effects of permafrost degradation on soil enzymes in peatlands, ten peatlands from three types of permafrost regions along the permafrost degradation sequence (predominantly continuous permafrost region-predominantly continuous and island permafrost region-sparsely island permafrost region) in northeast China were selected to examine the activities of soil invertase, β-glucosidase, urease and acid phosphatase and their relationships with soil physicochemical properties. The results demonstrated that permafrost type had significant effect on soil enzyme activities. Soil enzyme activities in predominantly continuous and island permafrost region were significantly higher than those in sparsely island permafrost region and predominantly continuous permafrost region. The activities of four soil enzymes were higher in 0–15 cm than 15–30 cm soil layer. Soil enzymes activities were positively correlated with soil ammonia nitrogen (NH4+-N), soil moisture content (SMC), total phosphorus (TP) and total nitrogen (TN), but negatively correlated with soil nitrate nitrogen (NO3−-N). Soil inorganic nitrogen and moisture contents were the main factors affecting soil enzyme activities, with NH4+-N accounted for 41.6% of the variance, SMC 29.6%, and NO3−-N 11.0%. These results suggested that permafrost degradation may change soil enzyme activities by changing soil physicochemical properties. In this study, only 0–30 cm peat soil in permafrost regions was collected during the complete thawing period of permafrost active layer, further studies should be placed on the change of soil enzyme activities in active layer and permafrost layer during freezing and thawing process in the southernmost location of northeast China in the Eurasia permafrost body and boreal forest belt.